Endogenous Borrowing Constraints, Human Capital Investment and Optimal Income Taxation - Hongyan Yang (Verein für Socialpolitik, 2010)
This paper employs a two-period life-cycle model to derive the optimal tax policy when educational investments are subject to endogenous credit constraints. Credit constraints arise from the limited commitment of creditors to repay loans and from the moral hazard problem due to private information on learning effort and work effort. We show that optimal tax policy differ from that in a similar model with exogenous credit constraints. In particular, if the welfare gain of subsidizing labor income by relaxing credit constraints dominates the welfare loss of increasing borrowing demand, regressive taxation is optimal. The reason is that subsidizing labor income increases the incentive to invest in education and to work, thus mitigating the moral hazard problem adherent to credit for educational investment. Furthermore, we find that no intervention could be optimal even if private capital market is imperfect.
Keywords: H21; I28; J00; 330; labor taxation; human capital investment; credit constraints